Facial nerve stimulation following cochlear implantation for X-linked stapes gusher syndrome leading to identification of a novel POU3F4 mutation. (December 2016) - Wester, Jacob L.; Merna, Catherine; Peng, Kevin A.; Lewis, Rebecca; Sepahdari, Ali R.; Ishiyama, Gail; Hosokawa, Kumiko; Kumakawa, Kozo; Ishiyama, Akira
Abstract: We report a case of a nine-year-old male who presented with facial nerve stimulation four years after cochlear implantation. Computed tomography was performed revealing a dilated internal auditory meatus and the cochlear implant electrode was found to be protruding into the fallopian canal at the level of the geniculate ganglion. Subsequent genetic analysis demonstrated X-linked deafness type 2 (DFNX2) caused by a novel c.769C > T nucleotide change in the POU domain, class 3, transcription factor 4 gene (POU3F4). Inactivation of electrodes 1 and 19–21 successfully abated facial nerve stimulation.